Toll-like receptor 9 (TLR9) gene deletion-mediated fracture healing in type II diabetic osteoporosis associates with inhibition of the nuclear factor-kappa B (NF-κB) signaling pathway. Issue 5 (2nd May 2022) - Han, Jiakai; Zheng, Qian; Cheng, Yongxia; Liu, Yong; Bai, Yuxin; Yan, Bin; Guo, Sufen; Yu, Jianbo; Li, Xinxin; Wang, Chong
ABSTRACT: Diabetes is characterized by increased fracture risk. Evidence from in vivo studies is lacking for anti-fracture strategies in diabetes. Our microarray analyses predicted association of Toll-like receptor 9 (TLR9) with both diabetes and osteoporosis, which was the focus of this work in a murine model of type II diabetic osteoporosis (T2DOP). A T2DOP model with fracture was established in TLR9 knockout (TLR9 −/− ) mice, which were then treated with the NF-κB signaling pathway inhibitor (PDTC) and activator (TNF-α). The obtained data suggested that TLR9 knockout augmented regeneration of bone tissues and cartilage area in the callus, and diminished fibrous tissues in T2DOP mice. Moreover, TLR9 depletion significantly affected bone mineral density (BMD), bone volume/tissue volume (BV/TV), connectivity density, trabecular number, trabecular separation and trabecular thickness, thus promoting fracture recovery. Bone morphology and structure were also improved in response to TLR9 depletion in T2DOP mice. TLR9 depletion inactivated NF-κB signaling in T2DOP mice. PDTC was found to enhance fracture healing in T2DOP mice, while TNF-α negated this effect. Collectively, these data indicate that TLR9 depletion may hold anti-fracture properties, making it a potential therapeutic target for T2DOP. Abbreviations: Diabetic osteoporosis (DOP); bone mineral density (BMD); Toll-like receptors (TLRs); type 2 diabetes (T2D); Toll-like receptor 9 (TLR9); nuclear factor-kappaB (NF-κB); streptozotocin (STZ); type 2 diabetic osteoporosis (T2DOP); Gene Expression Omnibus (GEO); Kyoto encyclopedia of genes and genomes (KEGG); pyrrolidine dithiocarbamate (PDTC); computed tomography (CT); Hematoxylin–eosin (HE); bone morphogenetic protein 7 (BMP7); analysis of variance (ANOVA); Graphical abstract: uf0001